2008
DOI: 10.1152/ajpheart.00999.2007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of atrial fibrillation: a comparison of two pacing models

Abstract: is a well-established animal model of atrial fibrillation (AF). However, this model is limited by a high mortality rate and severe heart failure. The purpose of our study was to assess a new canine model of inducible AF. We performed acute, short-term, simultaneous atrioventricular pacing (SAVP) and RVP (in random order) in 14 dogs for 30 s. SAVP produced more echocardiographic pulmonary venous flow reversal, a greater increase in mean pulmonary capillary wedge pressure, and a significantly greater decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…[20][21][22] Patients with both chronic rheumatic heart disease and AF showed abnormal expression of MMP-1, 23 and MMP-9 has been associated with rapid atrial arrhythmia. 24,25 In an animal model of rapid atrial pacing-induced atrial failure, MMP-9 activity in the atrial intramuscular matrix increased by 50% compared with sinus rhythm, while levels of specific tissue inhibitors decreased by 50%. 26 Another study has shown that MMP inhibitors can decrease left ventricular dilatation and wall thinning of heart failure induced by overdrive pacing, to reduce atrial chamber wall stress.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Patients with both chronic rheumatic heart disease and AF showed abnormal expression of MMP-1, 23 and MMP-9 has been associated with rapid atrial arrhythmia. 24,25 In an animal model of rapid atrial pacing-induced atrial failure, MMP-9 activity in the atrial intramuscular matrix increased by 50% compared with sinus rhythm, while levels of specific tissue inhibitors decreased by 50%. 26 Another study has shown that MMP inhibitors can decrease left ventricular dilatation and wall thinning of heart failure induced by overdrive pacing, to reduce atrial chamber wall stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this MR contributes to the significant left atrial dilation that occurs with chronic rapid pacing, and in turn may contribute to the atrial arrhythmogenicity of this pacing-induced DCM model [34,[46][47][48][49][50], which is discussed in a subsequent section. It is now well recognized that MR in and of itself can contribute to the progression of CHF secondary to clinical forms of DCM.…”
Section: Cellular and Biochemical Considerations To Chronic Rapid Pacingmentioning
confidence: 99%
“…The pacing-induced DCM model has been demonstrated to develop an arrhythmia-susceptible substrate [34,[46][47][48][49][50]. For example, Balaji et al reported a higher incidence of inducibility of ventricular arrhythmias and increased mortality due to refractory ventricular fibrillation in pigs with pacing DCM [34].…”
Section: Electrophysiology and Arrhythmogenesis In Chronic Rapid Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dangerous cardiac arrhythmias, such as atrial and ventricular fibrillation have been frequently associated to fibrosis [26,9,14,24]. For instance, during atrial fibrillation the duration of fibrillation episodes was highly correlated to the degree of fibrosis, i.e.…”
Section: Introductionmentioning
confidence: 99%